PERAN NINIK MAMAK,MAMAK DAN KAMANAKAN DI MINANGKABAU - Muhammad Chairul Umar; Yulfira Riza (Universitas PGRI Adi Buana Surabaya, 2022)
In Minangkabau the role of ninik mamak, mamak and kamanakan is very important. For example, when there is a problem between communities, it is Ninik Mamak who will handle it. So what's the difference between ninik mamak and mamak? So Ninik mamak consists of several penghulu, existing tribes, while the mamak is the mother's brother. Ninik mamak are elders in the tribe and in their nagari, usually ninik mamak are traditional leaders in Minang whose leadership is usually traditional, the position of ninik mamak is usually different, some are equal and some are tiered. This article aims to determine the role of ninik mamak, mamak and kamanakan both in terms of function and meaning. Method From writing this article using the library, namely reading existing sources such as articles related to the theme. In Minang, the role of mamak is very important to the child. Mamak, will teach all things about the norms that exist in the family, with that kamanakan who will carry on for the next if Mamak is no longer there. and the mamak acts as a protector for her sisters and keeps the inheritance, then as a mamak, she must set a good example for her kamanas so that her kamanas will emulate her mamak's attitude. With a good upbringing from mamak then kamanakan will be noticed by the community